Sentiment Analysis on Jurassic Park Development in the Komodo Conservation Area - Annisa Septiana Sani; Indra Budi (Universitas Respati Yogyakarta, 2022)
Rinca Island is included in one of the islands in NTT Province, which is used as a National Park to protect Komodo dragons. According to the government's agenda, in June 2021, Rinca Island will build a world-class premium tourist destination project for tourists who want to see Komodo, which is called Jurassic Park Komodo. The existence of tourism is expected to be able to attract tourists and investment. However, the news about project development that is not in accordance with the conservation value has created public sentiment towards the project development process. The purpose of this study is to analyze public sentiment related to the classification of support & against the development of Jurassic Park in the Komodo Conservation Area and to measure the accuracy using two methods, namely Naïve Bayes and Decision Tree.